Implementasi Gaya Kepemimipinan Karismatik Kepala Sekolah dalam Peningkatan Peserta Didik Baru SMK Muhammadiyah 1 Randublatung Kabupaten Blora - Rasini, Rasini; Egar, Ngasbun; Wuryandini, Endang (PGRI Kota Semarang, 2024)
The purpose of this research is to find out about: (1) The school principal's management creates better changes in increasing new students at SMK Muhammadiyah 1 Randublatung including planning, Organizing, actuating and controlling. (2) The principal's management builds trust increasing new students at SMK Muhammadiyah 1 Randublatung including planning, organizing, actuating, and controlling. (3) The principal's management builds a commitment to increasing new students at SMK Muhammadiyah 1 Randublatung including planning, Organizing, actuating and controlling. This research uses a qualitative approach. The subject of this research was the principal of SMK Muhammadiyah 1 Randublatung and the informants consisted of teachers, education staff and students. The data collection techniques used were interviews, observation and documentation. The data analysis used is data collection, data condensation, data presentation and drawing conclusions. From the results of this research it can be seen that the number of new students has increased because the principal with his charismatic leadership style has implemented POAC well and has also made changes in the school such as school facilities and infrastructure, as well as new school programs, building trust in the integrity and competence of the principal also builds commitment with high loyalty to the organization, always provides motivation and inspiration to teachers and students, and is a person who works hard. Keywords: charismatic leadership style, increasing new students.